Образ „гордой полячки” в пьесе Леонида Зорина „Варшавская мелодия” - Popovich, Natalia (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
Helena is the main character of this play and she is the author’s porte parole.This character develops stereotype of „a proud Polish woman” and continues the19th century plot in Russian literature (the relationship of a strong woman and a weakman). The main character’s features are: sacrifice, ability to love and forgive, will to fight for personal matters. In Warsaw melody we can see that love and social themes are bound together — the conflict is not between person, but a man and the country. A Polish woman is a symbol of higher culture, she wants to overcome fear of what happens tomorrow, that is induced by her WWII life history, and gains life experience due to herpossibility to analyze and summarize. In the text we can find the author’s allusionsto the tragic history of Poland during WWII.